Preparation of TiO2 compact layer by heat treatment of electrospun TiO2 composite for dye-sensitized solar cells - Mustafa, Muhammad Norhaffis; Shafie, Suhaidi; Wahid, Mohd Haniff; Sulaiman, Yusran (Elsevier, 2020)
The power conversion efficiency (PCE) of the dye-sensitized solar cell was improved by using titanium dioxide (TiO2) compact layer prepared via heat treatment assisted electrospinning. Titanium tetraisopropoxide mixed with polyvinyl-alcohol was used as the electrospun solution. In this study, TiO2 photoanode with TiO2 compact layer was compared with TiO2 photoanode without TiO2 compact layer where the PCE was improved by 76.88%. Electrochemical impedance spectroscopy proved that the TiO2 compact layer can reduce the series resistance and improved the short circuit current density, resulting in a low recombination effect that leads to a higher PCE. The electron lifetime and charge collection efficiency of TiO2 nanoparticles with TiO2 compact layer displayed a higher value compared to TiO2 nanoparticles without TiO2 compact layer.